Marine mammal research and conservation in Sri Lanka 1985-1986 - Leatherwood, Stephen; Reeves, Randall R. (Narrobi, Kenya UNEP, 1991)
Marine Mammal Technical Report Number 1
Keywords: Marine mammals--Research--Sri Lanka; Marine mammals--Conservation--Sri Lanka